Development of Picture Story Book Learning Media as Literacy Material for Earthquake Disaster Mitigation Students of Tegal Ratu Cilegon State Elementary School Banten - Wukufahdini Trijayanti; Muzani Muzani; Cecep Kusnadi (Green Publisher Indonesia, 2025)
This research on the development of picture storybook media aims to provide education as literacy material for elementary school students regarding earthquake disaster mitigation, especially in the Cilegon area, Banten, which is one of the earthquake-prone areas. This research aims to develop a picture storybook media entitled